Outcome of cataract surgery in patients with retinitis pigmentosa. Issue 8 (1st August 2001) - Jackson, H; Garway-Heath, D; Rosen, P; Bird, A C; Tuft, S J
Abstract : AIM: To determine the visual benefit of cataract extraction in patients with retinitis pigmentosa and to identify risk factors for poor outcome. METHODS: A retrospective analysis was undertaken of a continuous series of 142 eyes of 89 patients with retinitis pigmentosa undergoing cataract surgery between 1985 and 1997. RESULTS: Mean age at surgery was 47.5 years (range 24–81 years). In 100 eyes there was posterior subcapsular lens opacity alone, 37 eyes also had moderate nuclear sclerosis, and five had only nuclear sclerosis. All patients had central visual fields of <10°. Overall, mean visual acuity improved from 1.05 (SD 0.38) preoperatively to 0.63 (SD 0.49) postoperatively on the logMAR scale. Significant postoperative capsular opacification occurred in 88/139 eyes (63%) and 45.1% required capsulotomy. Anterior capsulotomy was undertaken in 5/52 (9.6%) eyes undergoing phacoemulsification. Postoperative macular oedema was noted in 20 (14%) eyes. Visual acuity improved in 109 eyes (77%), was unchanged in 29 eyes (20.5%), and worsened after surgery in four eyes (2.5%). 86/89 patients reported major improvement of visual function. CONCLUSIONS: Cataract surgery for relatively minor lens opacities is beneficial in patients with retinitis pigmentosa, and most report subjective improvement of visual symptoms. The incidence of capsular opacification is high and anterior capsular contraction may occur. The number of eyes with poor vision due to macular oedema was unexpectedly low.